The gene encoding the epsilon subunit of the T3/T-cell receptor complex maps to chromosome 11 in humans and to chromosome 9 in mice. - Gold, D P (1987)
The T3 complex is composed of three polypeptide chains that are both structurally and functionally associated with the receptor for antigen on the surface of human T lymphocytes. In a series of experiments utilizing both somatic cell hybrids and chromosomal hybridization in situ, the genes encoding two members of the human T3 complex, T3-delta and T3-epsilon, were found to reside on the long arm of chromosome 11 in band q23. The murine T3-epsilon gene was localized to chromosome 9. The location of the T3-delta and T3-epsilon genes with respect to the Hu-ets-1 gene, which is also located in 11q23, is discussed. Recent assignments of several genes, preferentially expressed in human cells of hematopoietic and neuroectodermal origins, to band q23 of human chromosome 11 and the murine equivalents to murine chromosome 9 may define a conserved gene cluster important in cell proliferation and differentiation.